PENGEMBANGAN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) MODEL PEMBELAJARAN RECIPROCAL TEACHING PADA MATA KULIAH DOKKAI 3 - Wirna, Yurmai; Charlina, Charlina; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstrack:This research is describing the product development of Learning Implementation Plans (RPP) using a learning model that has never been applied to the dokkai 3 course before, namely the reciprocal teaching. This research includes level 3 research and development (R&D) research, which is developing existing products and also making and testing the effectiveness of these products. The data sources in this study were RPP development media experts and dokkai material experts, as well as 9 Japanese Language Education students from the Riau University FKIP year 2019 as respondents. Data collection was carried out with a questionnaire validation test of the feasibility of media development experts and material experts, students response questionnaires, and observations during the learning process. The data analysis in this study is in the form of qualitative descriptive, and quantitative data techniques by carrying out the product development process in accordance with the procedures of the level 3 Development research is carried out continuously until the product lesson plans are declared suitable for use in the dokkai 3 learning process.Key Words: research and development(R&D), RPP, reciprocal teaching, dokkai